2008
DOI: 10.1007/s00436-008-1215-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Cryptosporidium isolates from pigs at slaughterhouses in South Bohemia, Czech Republic

Abstract: A total of 123 fecal samples of slaughtered finisher pigs and 21 sows from 14 farms were screened for Cryptosporidium spp. infection using the aniline-carbol-methyl violet staining method. Positive samples were molecularly characterized by direct sequencing of partial small subunit ribosomal RNA (SSU rRNA) and GP60 partial genes and polymerase chain reaction restriction fragment length polymorphism of SSU rRNA. Cryptosporidium oocysts were microscopically identified in 36 finishers (29%) and two sows (10%). Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 24 publications
6
31
0
2
Order By: Relevance
“…Co-infections in pigs caused by these two parasites were previously described by Němejc et al (2013). C. parvum is not considered as a frequent swine parasite, but it was occasionally found in pigs housed in Europe (Maddox-Hyttel et al 2006, Zintl et al 2007, Kváč et al 2009b) and Canada (Budu-Amoako et al 2012). In this study, C. parvum was detected once in a five-month-old finisher pig with diarrhoea.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Co-infections in pigs caused by these two parasites were previously described by Němejc et al (2013). C. parvum is not considered as a frequent swine parasite, but it was occasionally found in pigs housed in Europe (Maddox-Hyttel et al 2006, Zintl et al 2007, Kváč et al 2009b) and Canada (Budu-Amoako et al 2012). In this study, C. parvum was detected once in a five-month-old finisher pig with diarrhoea.…”
Section: Discussionsupporting
confidence: 59%
“…Another species frequently infecting pigs is C. suis (Suárez-Luengas et al 2007, Santín and Trout 2008, Kváč et al 2009a). Except specific Cryptosporidium, adapted to a swine host, other species or genotypes such as C. parvum, C. muris, Cryptosporidium mouse genotype I, C. felis and Cryptosporidium rat genotype have been occasionally detected in pigs (Chen and Huang 2007, Zintl et al 2007, Kváč et al 2009b, Jenkins et al 2010. The sporadic findings of C. parvum may indicate that pigs can also serve as an animal reservoir for human cryptosporidiosis (Maddox-Hyttel et al 2006, Zintl et al 2007, Kváč et al 2009b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main Cryptosporidium species identified in pigs in Australia and worldwide are C. suis and pig genotype II, although C. muris, C. tyzzeri and C. parvum have also been reported Zintel et al 2007;Johnson et al 2008;Kvác et al 2009a;Jeníková et al 2010;Jenkins et al 2010;Sevá Ada et al 2010;Xiao, 2010;Wang et al 2010a;Budu-Amoako et al 2012;Chen et al 2011;Farzan et al 2011;Fiuza et al 2011a;Yin et al 2011). Cryptosporidium suis has been reported in humans (Xiao et al 2002a;Xiao, 2010) and has frequently been recovered from water samples (Feng et al 2011a).…”
Section: Feral and Domestic Pigsmentioning
confidence: 99%
“…Thus, C. parvum remains largely a parasite of humans and preweaned calves, with some recent studies showing that it may sometimes be found in sheep, goats, horses, and alpacas (17,39,45,55,57). In a survey conducted in the Czech Republic by Kváč et al (32), C. parvum subtype IIaA16G1R1b was found in 2/21 sows and 0/123 slaughtered finishers from 14 pig farms. In contrast, Cryptosporidium pig genotype II was detected in 36 finishers, 15 of which had concurrent infection with Cryptosporidium suis.…”
Section: Genotyping and Molecular Epidemiologymentioning
confidence: 99%